The Influence Of Sustainability Report Disclosure, Firm Size, And Green Accounting On Return on Assets Of Companies In Basic Materials Sector In 2020-2024 - Muhammad Yudhistira; Soegiharto Soegiharto (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to analyze the effect of Sustainability Report Disclosure, Firm Size, and Green Accounting on Return on Assets (ROA) of basic materials sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. Design/methodology/approach – This research employs a quantitative approach with causal-explanatory design using secondary data obtained from annual reports and sustainability reports. The sample consists of 16 basic materials sector companies selected using purposive sampling technique, resulting in 80 observations during 2020-2024. Data analysis was conducted using panel data regression with Random Effect Model (REM) approach, supported by EViews9 software. Variable measurement uses disclosure index based on GRI Standards 2021 for Sustainability Report, natural logarithm of total assets for Firm Size, and dummy variable for Green Accounting based on environmental cost disclosure. Findings – The results showed that the overall model was significant (F-statistic = 2.245; p-value = 0.090), explaining 8.14% of the variation in ROA (R² = 0.814). Individually, the Sustainability Report Disclosure variable had no effect on ROA (coefficient = 0.0034; p-value = 0.4998), indicating that corporate sustainability transparency has not been able to improve asset profitability. Firm size did not affect ROA (coefficient = 0.0008; p-value = 0.6878). The results showed that firm size does not directly reflect a company's ability to generate profits from its assets. On the other hand, Green Accounting shows a negative effect on ROA (coefficient = -0.0608; p-value = 0.0163), this can be interpreted that the costs arising from the implementation of Green Accounting in the short term have the potential to reduce the company's profitability, although in the long term it can provide non-financial benefits such as reputation and business sustainability. Practically, companies that implement Green Accounting (disclose environmental costs in sustainability reports) have a lower ROA of 6.1 points compared to companies that do not implement it, assuming other variables are constant. Research limitations/implications – This research was obtained from financial reports and sustainability reports. The data obtained only covers a five-year period and may not fully capture the quality or substance of the disclosures, but only the quantity. JEL: G3, Q5